Simulation for the production of synthetic natural gas for vehicles (SNGV) from palm waste via gasification with in-situ CO2 capture - Inayat, A. (Institute of Electrical and Electronics Engineers Inc., 2017)
Due to abundance of oil palm waste worldwide, it is a good candidate to be used as a feedstock for synthetic natural gas for vehicles (SNGV) production. Biomass gasification is one of the promising methods for SNGV production. This work focuses on the gasification with in-situ CO2 capture using CaO as absorbent materials for SNGV production from palm oil empty fruit bunch (EFB). Two parameters (temperature 500-900°C and steam/biomass ratio 1-2.2) have been studied on the production of SNGV via simulation approach in ASPEN HYSYS. The model has been also validated with literature and showed good agreement. The results showed that the EFB has good potential to produce higher yield of SNGV at lower temperature. The higher value of SNGV (4 kg/hr) is obtained due to the lower concentration of CO2 caused by using CaO as sorbent material. © 2017 IEEE.